Clinical Pharmacology of Midazolam in Neonates and Children: Effect of Disease—A Review. (18th February 2014) - Pacifici, Gian Maria
Abstract : Midazolam is a benzodiazepine with rapid onset of action and short duration of effect. In healthy neonates the half-life ( t 1/2 ) and the clearance (Cl) are 3.3-fold longer and 3.7-fold smaller, respectively, than in adults. The volume of distribution (Vd) is 1.1 L/kg both in neonates and adults. Midazolam is hydroxylated by CYP3A4 and CYP3A5; the activities of these enzymes surge in the liver in the first weeks of life and thus the metabolic rate of midazolam is lower in neonates than in adults. Midazolam acts as a sedative, as an antiepileptic, for those infants who are refractory to standard antiepileptic therapy, and as an anaesthetic. Information of midazolam as an anaesthetic in infants are very little. Midazolam is usually administered intravenously; when minimal sedation is required, intranasal administration of midazolam is employed. Disease affects the pharmacokinetics of midazolam in neonates; multiple organ failure reduces the Cl of midazolam and mechanical ventilation prolongs the t 1/2 of this drug. ECMO therapy increases t 1/2, Cl, and Vd of midazolam several times. The adverse effects of midazolam in neonates are scarce: pain, tenderness, and thrombophlebitis may occur. Respiratory depression and hypotension appear in a limited percentage of infants following intravenous infusion of midazolam. In conclusion, midazolam is a safe and effective drug which is employed as a sedative, as antiepileptic agent, for infants who are refractory to standard antiepileptic therapy, and as an anaesthetic.